2022
DOI: 10.12973/eu-jer.11.2.1009
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Professional Learning Community of Pedagogical Instructors, Training Teachers and Teaching Students within a Clinical Model for Teacher Education to Their Professional Development

Abstract: <p style="text-align: justify;">The purpose of the present study is to examine the contribution of professional learning community of pedagogical instructors, training teachers, and teaching students in clinical model for teacher education to their professional development. The prior is carried out through examining a variety of categories: namely, collaborative learning, personal responsibility, collective responsibility, reflective pedagogical discourse and action research, knowledge development and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…These high percentages indicate that the contribution of the clinical model to the professional development of teaching students is effective in the dimensions active participation and collaborative learning, personal and collective responsibility, active research (applied research), clinical thinking and SEL, and the role of the training teacher. These findings are consistent with those reached by Murad et al (2022), who concluded that the learning community of the clinical model of teacher education contributed significantly to the professional development of all participants regardless of their field of knowledge, the role in the training process, and the methodological activities offered by colleges and schools.…”
Section: Resultssupporting
confidence: 91%
“…These high percentages indicate that the contribution of the clinical model to the professional development of teaching students is effective in the dimensions active participation and collaborative learning, personal and collective responsibility, active research (applied research), clinical thinking and SEL, and the role of the training teacher. These findings are consistent with those reached by Murad et al (2022), who concluded that the learning community of the clinical model of teacher education contributed significantly to the professional development of all participants regardless of their field of knowledge, the role in the training process, and the methodological activities offered by colleges and schools.…”
Section: Resultssupporting
confidence: 91%
“…Teacher professional development can also facilitate partnerships between community organizations and schools [3,6]. By incorporating community partners into professional development spaces, teachers have the potential to learn about new forms of instruction, collaboration, and knowledge, regardless of the field of study [12]. Morrissey and Kenny [13] describe an example of utilizing community partners in professional development settings, finding that art teachers who participated in a partnership with local artists expanded their pedagogical methods and felt more confident in their ability to teach their lessons.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to strengthen skills and competencies in higher education to satisfy the workforce demands of an increasingly globalized world. Educators should help students to face the challenge of interacting with diverse cultures, and it is essential to prepare them with a perspective of collaborative work to develop common solutions, promoting better working relationships [2]. For instance, with the current challenges, to be competitive, companies and institutions need to develop international collaboration strategies and alliances, which requires the effective execution of collaborative work competences [3].…”
Section: Introductionmentioning
confidence: 99%